Critical care nursing : a holistic approach 2026-02-15T13:38:45+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Fontaine, Dorrie K.; Morton, Patricia Gonce, 1952- (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)

(untitled)
Now in its Ninth Edition, this classic text and reference maintains its popular holistic approach to the complexities of critical care nursing. The book's comprehensive coverage begins with the psychosocial concepts of care and progresses through assessment and management of a variety of disorders. The Ninth Edition has additional full-color art and has been thoroughly updated. Highlights include new chapters on disaster management and end-of-life care; expanded coverage of evidence-based practice, ethics, and computerized charting; new information on bariatric surgery; and discussions of pediatric considerations. This edition also includes NCLEXr-style questions. - Publisher